2016
DOI: 10.1080/09513590.2016.1177009
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postpartum glucose intolerance in women with gestational diabetes mellitus

Abstract: II measured by OGTT during pregnancy might be a useful predictor of GI within the early postpartum period in women with GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 18 publications
6
17
2
1
Order By: Relevance
“…Previous studies have shown the prevalence rates of glucose intolerance (i.e. diabetes and impaired glucose tolerance/impaired fasting glucose) during the early postpartum period in Japanese women with GDM to be 16.7% , 27.1% and 34.3% . The prevalence of glucose intolerance in the present investigation was similar to or slightly higher than those of previous studies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previous studies have shown the prevalence rates of glucose intolerance (i.e. diabetes and impaired glucose tolerance/impaired fasting glucose) during the early postpartum period in Japanese women with GDM to be 16.7% , 27.1% and 34.3% . The prevalence of glucose intolerance in the present investigation was similar to or slightly higher than those of previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies suggest that insulinogenic index is a useful predictor of early postpartum glucose intolerance in Japanese women with GDM [16,17]. In the present study, the insulinogenic index in the glucose intolerance group was lower than that in the normal glucose tolerance group, but the difference was not statistically significant (P=0.056).…”
Section: Discussioncontrasting
confidence: 77%
“…Breastfeeding is a convenient and low‐cost method of improving postpartum health. However, many studies that analyzed the risk factors for progression of GDM to type 2 diabetes mellitus overlooked the mother's lactation status. Mothers with prior GDM were less likely to breast‐feed their children than mothers without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the susceptibility to glucose intolerance varies among different racial or ethnic groups, the clinical risk factors and genetic variants of pAGT might differ between Caucasian and Japanese women. However, few reports on the risk factors of pAGT are available with regard to Japanese women with GDM, and, to the best of our knowledge, there are no data on the genetic variants associated with pAGT in this population subgroup.…”
Section: Introductionmentioning
confidence: 99%
“…However, the rate of postpartum follow up for women with GDM is low; therefore, it is desirable to identify those at the greatest risk by determining the risk factors 3 . The clinical risk factors associated with postpartum abnormal glucose tolerance (pAGT) include a family history of diabetes, obesity, early GDM diagnosis, fasting hyperglycemia, insulin requirement during pregnancy and antepartum b-cell dysfunction [4][5][6][7][8][9][10][11][12][13] . Additionally, recent studies have shown that certain genetic variants are associated with the development of future type 2 diabetes mellitus in women with a history of GDM 9,14,15 .…”
Section: Introductionmentioning
confidence: 99%